Feasibility studies on the uptake and bioaccessibility of pesticides, hormones and endocrine disruptive compounds in plants, and simulation of gastric and intestinal conditions - Chormey, Dotse Selali; Ayyildiz, Merve Firat; Bakirdere, Sezgin (ELSEVIER, 2020)
Large scale productions made by industries to meet the needs of the ever growing human population has led to the contamination of environmental resources such as water, air, soil and forests. These contaminants pose health risks to humans and they are capable of entering the food chain through aquatic organisms and by the uptake in plants. This study investigated the uptake of alkylphenols, hormones, pesticides and bisphenol A by plants grown in soilless media under laboratory conditions. Green onion and lettuce were selected for this purpose due to their high water intake rate. Optimum parameters of a dispersive liquid-liquid microextraction method were applied to aqueous samples to lower detection limits for the analytes determined by gas chromatography mass spectrometry. Analysis performed on the plant media on alternate days suggested migration of the analytes into the plants and this was confirmed by results (0.59-6.4 mu g/g) obtained for analyzed plant samples at the end of the study. The plants were then treated in simulated gastric and intestinal conditions, and the results obtained suggested degradation of the analytes with time. This is the first comprehensive study on the migration of different environmental contaminants into plants and the changes they undergo when ingested into the stomach.
Keywords: Alkylphenols; Endocrine disruptive compounds; Hormones; Pesticides; Simulated gastric conditions; ORGANOCHLORINE PESTICIDES; POLYCHLORINATED-BIPHENYLS; METABOLITES; VALIDATION; Chemistry